Mircea Eliade Between Political Journalism and Scholarly Work - Oișteanu, Andrei (Archaeus, 2004)
Christianity did not, as a rule, serve the nationalistic ideologies evolving in late 19th century Europe, which degenerated into fascist regimes during the inter-war period. Christianity was perceived as an "international" religion, unable to appropriately serve nationalistic and ethnocratic doctrines. As a pacifist doctrine, preaching resignation and tolerance, Christianity did not match the "heroic" and martial feeling that was seizing Europe at the time. Christian philosophy, urging people to "love their neighbor" and "turn the other cheek", was in total disagreement with the cult of violence, the militancy and the virility preached by the new prophets of neo-paganism (speaking, in 1938, about the "legionary aristocracy", Eliade would use such phrases as "promoting manhood and an offensive spirit", "heroism", "the birth of a new elite, who is conquering its freedom by learning to die and sacrifice themselves" etc.).